Cyclin H expression is increased in GIST with very-high risk of malignancy - Dorn, Julian (BioMed Central, 2010)
BACKGROUND: Risk estimation of gastrointestinal stromal tumours (GIST) is based on tumour size and mitotic rate according to the National Institutes of Health consensus classification. The indication for adjuvant treatment of patients with high risk GIST after R(0 )resection with small molecule inhibitors is still a controversial issue, since these patients represent a highly heterogeneous population. Therefore, additional prognostic indicators are needed. Here, we evaluated the prognostic value of cyclin H expression in GIST. METHODS: In order to identify prognostic factors of GIST we evaluated a single centre cohort of ninety-five GIST patients. First, GISTs were classified with regard to tumour size, mitotic rate and localisation according to the NIH consensus and to three additional suggested risk classifications. Second, Cyclin H expression was analysed. RESULTS: Of ninety-five patients with GIST (53 female/42 male; median age: 66.78a; range 17-94a) risk classification revealed: 42% high risk, 20% intermediate risk, 23% low risk and 15% very low risk GIST. In patients with high risk GIST, the expression of cyclin H was highly predictive for reduced disease-specific survival (p = 0.038). A combination of cyclin H expression level and high risk classification yielded the strongest prognostic indicator for disease-specific and disease-free survival (p ≤ 0.001). Moreover, in patients with tumour recurrence and/or metastases, cyclin H positivity was significantly associated with reduced disease-specific survival (p = 0.016) regardless of risk-classification. CONCLUSION: Our data suggest that, in addition to high risk classification, cyclin H expression might be an indicator for "very-high risk" GIST.